2021
DOI: 10.1002/celc.202100083
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Current Density of Oxygen Reduction under Ultrathin Electrolyte Layers: From the Micrometer Range to Monolayers

Abstract: The oxygen reduction reaction (ORR) under ultrathin electrolyte layers is a key reaction in many processes, from atmospheric corrosion to energy conversion in fuel cells. However, the ORR current under ultrathin electrolyte layers is difficult to measure using conventional electrochemical methods. Hence, reliable data are scarce for the micrometer range and totally missing for the sub‐micrometer range of the electrolyte layer thickness. Here, we report a novel hydrogen‐permeation‐based approach to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The Pd foil was cleaned in situ via electrochemical cyclic voltammetry (CV) method by running 50 cycles with each scan from −1 V to 0.5 V at 50 mV s −1 scan rate. 19 Hydrogen formation reaction kinetics was enabled by potentiostatic charging on the entry cell (since hydrogen enters the Pd membrane from this side) in N 2 atmosphere. For the ORR kinetic study, galvanostatic charging method was adopted in the entry cell and the recorded current density "I" was considered as the hydrogen oxidation as well as oxygen reduction current based on our previous work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pd foil was cleaned in situ via electrochemical cyclic voltammetry (CV) method by running 50 cycles with each scan from −1 V to 0.5 V at 50 mV s −1 scan rate. 19 Hydrogen formation reaction kinetics was enabled by potentiostatic charging on the entry cell (since hydrogen enters the Pd membrane from this side) in N 2 atmosphere. For the ORR kinetic study, galvanostatic charging method was adopted in the entry cell and the recorded current density "I" was considered as the hydrogen oxidation as well as oxygen reduction current based on our previous work.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen potentiometry (HP) was recently introduced by Vijayshankar et al 16 to measure ORR rate underneath organic coatings by using the hydrogen formation reaction (HFR) current evolved on the backside of a metal membrane as a proxy for the oxygen reduction reaction current on the polymer coated front side in a standard Devanathan-Stachurski double electrochemical cell. [16][17][18] This technique has also been recently developed to measure ORR rate underneath ultrathin electrolyte layers by X. Zhong et al 19 In this work, the novel hydrogen potentiometry (HP) technique 16 is combined with electrochemical impedance spectroscopy (EIS) to quantitatively characterize the oxygen reduction kinetics at a model polymethylmethacrylate (PMMA) coated palladium membrane and correlate it to the coating barrier properties to understand the degradation behaviour of the interface. It is shown that with increasing coating destruction by the oxygen reduction reaction, the PMMA/Pd interface charge transfer resistance also decreases and correlates well with the fast ORR kinetics measured via the currentpotential I(U) curve using the HP approach.…”
mentioning
confidence: 99%
“…Similarly, a liquid aqueous electrolyte is used at RDE, while MEA contains a solid electrolytic membrane known as a proton exchange membrane (PEM) for the better transport of reactants. Hence, reactants transport through liquid into the catalyst/electrode interface at RDE while it occurs through porous PEM at MEA 23 . Ambient working conditions are used at RDE, such as room temperature with standard pressure conditions.…”
Section: Oxygen Reduction Evaluation and Standard Protocolsmentioning
confidence: 99%
“…Hence, reactants transport through liquid into the catalyst/electrode interface at RDE while it occurs through porous PEM at MEA. 23 Ambient working conditions are used at RDE, such as room temperature with standard pressure conditions. Mass transport is smooth at RDE, where a rotating electrode results in quick mass transport across the electrolyte to generate a tiny current (less than 10 mAcm −2 ).…”
Section: Oxygen Reduction Evaluation and Standard Protocolsmentioning
confidence: 99%
“…20 Therefore, the transport of reactant gas depends on the solubility of oxygen in the electrolyte at the catalyst/ electrode interface in the RDE. 21,22 However, in MEA, oxygen is transported through micropores of the gas diffusion layer to the CL in a large flux, which suffers from significant resistance due to the membrane and CL texture. 9 The rotating electrode facilitates efficient mass transport of reactants to the ultrathin catalyst layer due to the low oxygen solubility in the aqueous electrolyte (resulting in a lower current density (less than 10 mA cm À2 )).…”
Section: Apparatus Differencesmentioning
confidence: 99%